2018
DOI: 10.18203/2320-1770.ijrcog20181358
|View full text |Cite
|
Sign up to set email alerts
|

Study of risk factors and tumor markers in ovarian malignancy in western part of Odisha: a prospective observational study

Abstract: Background: Ovarian cancer represents one of the most frequently seen malignancies in women and it is the fifth most common cause of cancer-related death in women. The aim of the study to determine the risk factors leading to ovarian cancer in western part of Odisha, India and show the tumour markers in this population.Methods: This is a prospective observational study included 240 ovarian masses diagnosed at Department of Obstetrics and Gynaecology, V. S. S. Medical College, Burla, Sambalpur over 3 years base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…11 But other researchers reported age of menarche to be having no effect on the risk of ovarian cancer. [8][9][10] The observation of present study that ovarian cancers are more common in postmenopausal women (65, 89%) also sits well with most of the available evidence. [8][9][10][11] Majority of patients (82.2%) in the present study did not use oral contraceptive pills.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…11 But other researchers reported age of menarche to be having no effect on the risk of ovarian cancer. [8][9][10] The observation of present study that ovarian cancers are more common in postmenopausal women (65, 89%) also sits well with most of the available evidence. [8][9][10][11] Majority of patients (82.2%) in the present study did not use oral contraceptive pills.…”
Section: Discussionsupporting
confidence: 91%
“…Majority of the patients were middle aged or elderly, which is in line with the earlier identified age groups for the disease. [8][9][10] Higher prevalence of ovarian cancer observed in women with one to two previous issues (64.3%) was also similar to the previous researchers' observations. 9,10 Mostly those with age at menarche between 13-14 years were found more prone for ovarian cancer in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, Kanupriya et al reported that most commonly encountered tumors of the ovary were the surface epithelial tumors (63%) followed by germ cell tumors (29%) in a total of 258 cases. (10) Also, Pradhan HK et al (11) showed that the prevalence of surface epithelial tumor was 70.2 % followed by germ cell tumor (28%); less common ovarian neoplasm were sex cord stromal tumors (1.8%) and metastatic tumor (0.4%). A study by Mondal et al 89 showed that out of 957 cases, surface epithelial tumors comprised 67.9% of all tumors and 73% of the malignant group.…”
Section: Discussion Smentioning
confidence: 99%